STUDENT`S GAINS OF DEBATING IN THE PRODUCTIVE LEARNING PROCESS - Samuseviča, Alīda; Ročāne, Maija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Publication highlights pedagogical possibilities of gaining transversal competences through debating process. Productive learning process has been described and data have gathered in order to identify the results of productive learning through debating. The necessity of productive learning has been emphasized in the context of key competencies and learning outcomes-based education approach as in the 21st century students need not only to take the initiative, understand the needs, formulate objectives, identify learning strategies, evaluate their learning achievements but also to explore a set of information offered by the information society which must be transformed into the knowledge society. The publication reflects the results of the case study, which emphasize obtaining the transversal skills through debating.